External Capital Structure : Theory and Evidence - Lane, Philip (IMF Working Papers; Working Paper, 2000)
Recent years have witnessed a change in the composition of capital flows to developing countries, and FDI and equity flows have been playing an increasing role. In this paper we discuss the challenges for international macroeconomics that these developments pose and characterize stylized facts associated with the structure of external liabilities in developing countries, focusing in particular on FDI and equity stocks.